Sergius of Reshaina : introduction to Aristotle and his Categories, addressed to Philotheos - Aydin, Sami, 1979- (Aristoteles Semitico-Latinus, 2016)
The physician and commentator Sergius of Reshaina (d. 536) composed two related texts in Syriac about the philosophy of Aristotle, chiefly dealing with themes discussed by Aristotle in his Categories , but also with his teaching on space as found in the Physics . This book presents a critical edition and English translation of the shorter of these texts. A survey of Sergius' life and works is given in the introduction and the intellectual context of his education in Alexandria is outlined, with focus on the medical and philosophical curricula of the Alexandrian school. Sergius' line of thought is clarified and his text is compared to Greek commentaries on the Categories that also present the teaching of his Neoplatonist master Ammonius Hermeiou.